74.5k views
22 votes
2x^2+8x-3=-1
Solve by completing the square.

User MickaelFM
by
5.0k points

1 Answer

5 votes

Answer:

step 1. Halve everything

x^2+ 4x - 0.5 = 0

step 2. Halve the coefficient of x so you can write down an equivalent for x² + 4 (that is, (x + 2)^2 - 4 )

(x + 2)² - 4.5 = 0

step 3. Isolate the squared term:

(x + 2)^2 = 4.5

step 4. Take square roots of both sides, recognising that a square root can be positive or negative:

x + 2 = ±√4.5

step 5. Make x explicitly

x = -2 ±√4.5

And there you are with two solutions.

Explanation:

hope this helps if not let me know have a great day

User Pita
by
5.5k points